Atributos do solo em sistema agroflorestal - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
With less land area and economic resources, family-based farmers were left out of the productive model based on the green revolution principles. For this group there is a need for alternative approaches aiming at sustainable rural development. Agroforestry systems bring together social, economic and environmental services and can be alternatives for rural development and sustainability. The objective of this study was to evaluate soil quality in a family agroforestry system using physical, chemical and biological indicators. The study was carried out in family farm located in the Contestado Settlement, in Lapa - PR. The climate of the region is classified as Cfb and the soil as a Cambisol. Four areas of the farm were selected, characterized by different soil uses and management: (a) agroforestry row with adoption time of 4 years (AR); (b) agroforestry inter-row with adoption time of 4 years (AI); (c) maize crop with conventional tillage (CT) and (d) native forest (NF). Soil density, total porosity, macroporosity, microporosity and bioporosity, and the chemical indicators pH, potential acidity (H+ + Al3+), calcium, magnesium, potassium, phosphorus, carbon and aluminum contents were measured at the layers 0-5, 5-10, 10-20 and 20-40 cm. In the 0-10 cm layer, saturated soil hydraulic conductivity (Kfs) and the biological indicators microbial biomass carbon, soil respiration, microbial quotient and metabolic quotient were measured. The visual evaluation of soil structure (VESS) was also performed. For the physical variables (with the exception of VESS and Kfs) and chemical variables, the principal component analysis (PCA) and hierarchical group analysis (AHA) were used. The other variables were submitted to analysis of variance and statistics of orthogonal contrasts. The native forest presented distinct pedogenetic characteristics. PCA indicated, in all layers, the existence of three groups with different variability: 1) NT, 2) AR and AI and 3) LA. The AHA confirmed the results reported in the PCA. Soil texture and chemical attributes of AR and AI were similar to CT. AI and CT showed limiting values of macroporosity in the 10-20 cm and 5-10 and 10-20 cm layer, respectively. In the layers 0-5 and 5-10 cm, AR and AI presented higher volume of biopores compared to CT. For Kfs, AI was the management that presented the lowest infiltration values, not differing from CT. Microbiological attributes did not differ between soil managements. The agroforestry row and inter-row presented better visual evaluation of the soil structure compared to the maize crop area.
Soil attributes in an agroforestry system
Keywords: Agricultura familiar; manejo do solo; qualidade de solo; desenvolvimento sustentável; Family farming; soil management; soil quality; sustainable development; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA